Ontologies of Rock Art Images, Relational Approaches, and Indigenous Knowledges - Moro Abadia, Oscar; Porr, Martin (Taylor & Francis, 2021)
Ontologies of Rock Art is the first publication to explore a wide range of ontological approaches to rock art interpretation, constituting the basis for groundbreaking studies on Indigenous knowledges, relational metaphysics, and rock imageries. The book contributes to the growing body of research on the ontology of images by focusing on five main topics: ontology as a theoretical framework; the development of new concepts and methods for an ontological approach to rock art; the examination of the relationships between ontology, images, and Indigenous knowledges; the development of relational models for the analysis of rock images; and the impact of ontological approaches on different rock art traditions across the world. Generating new avenues of research in ontological theory, political ontology, and rock art research, this collection will be relevant to archaeologists, anthropologists, and philosophers. In the context of an increasing interest in Indigenous ontologies, the volume will also be of interest to scholars in Indigenous studies.